Influence of extraction chambers backfilling on microclimat of deep mines - Лапшин, Александр Александрович (Eastern-European Journal of Enterprise Technologies, 2014)
To enhance the safety of underground works and save the earth surface from caving, mining enterprises perform underground ore extraction using backfilling. Together with a positive solution to the problem of mining safety and environmental improvement when using the backfilling system, there is a problem of heat emission during backfilling material hydration. To solve this problem, the studies of thermophysical properties of rocks of Kryvbas and Zaporozhye iron-ore plant, as well as backfilling materials, used to fill the worked-out space, are conducted. As a result of laboratory studies, the values of heat conductivity λ, W/m·K, heat capacity C, kJ/kgK and thermal diffusivity α, m2/s of rocks and backfilling materials are determined. Determining thermophysical properties of rocks and backfilling materials has allowed to define the boundaries of influence of backfill hydration heat in chambers on the surrounding rock mass. The way to reduce the temperature in exhaust chambers during hydration of solid backfill by adding crushed rocks from the developed deposit in the backfilling mixture is considered. Thus, by calculations and observations, it is found that using crushed rocks as the backfilling mixture component allows to reduce the zone of influence of backfill hydration on the temperature mode of adjacent mine workings up to 10 m.